LITERASI PENTINGNYA PEMAHAMAN INVESTASI OBLIGASI UNTUK KEBERLANGSUNGAN USAHA - Hastuti, Rini Tri; Triyana; Ferry Fernando (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
For students in school, the term bonds is more foreign to them than the term stocks, because stocks are mentioned more often. However, in reality, stocks and bonds are important instruments for companies and investors. Often students find it difficult when they start to enter the material on bonds in college. In addition to not being familiar with what bonds are, the calculations are also relatively difficult. The provision of material in this training is expected to provide knowledge that is not obtained in the material taught in class. The PKM topic that we will implement is training on the importance of understanding the form of bond investment to help the sustainability of a business. The topic given in this PKM activity is very important for two reasons: First, the material on investment in the form of bonds is not included in the basic accounting lesson material provided. Second, the majority of students' family backgrounds are entrepreneurs, thus increasing knowledge about the mechanism of investing in the form of bonds. In the business sector, investment in bonds can be one of the options besides investment in the form of fixed assets. For that, we, lecturers from the Faculty of Economics, will provide training which is planned to be divided into three stages, namely: planning stage, implementation stage, and review stage. The target outputs to be achieved from this training activity are: Mandatory outputs in the form of publications in the Serina journal and additional outputs in the form of IPR. ABSTRAK Bagi siswa di bangku sekolah, istilah obligasi mungkin belum dikenal daripada istilah saham, disebabkan saham lebih banyak dikenal. Namun kenyataannya saham dan obligasi adalah bagian aset yang penting bagi perusahaan dan juga investor. Seringkali siswa merasa kesulitan pada saat di bangku kuliah mulai memasuki materi obligasi. Selain mereka belum begitu mengetahui dan memahami apa itu obligasi, pengakuan, pencatatan nilai pun relatif komprehensif. Pemberian materi dalam pelatihan ini diharapkan dapat memberikan bekal pengetahuan yang tidak diperoleh dalam materi yang diajarkan di kelas. Topik PKM yang akan kami laksanakan adalah pelatihan mengenai pentingnya pemahaman mengenai bentuk investasi obligasi untuk membantu keberlangsungan sebuah usaha. Topik yang diberikan dalam kegiatan PKM ini sangat penting karena dua alasan: Pertama, materi mengenai investasi dalam bentuk obligasi belum termasuk ke dalam materi pelajaran akuntansi dasar yang diberikan. Kedua, latar belakang keluarga siswa mayoritas berwirausaha, sehingga menambah pengetahuan mengenai mekanisme berinvestasi dalam bentuk obligasi. Dalam bidang usaha, investasi dalam obligasi dapat menjadi salah satu opsi pilihan selain investasi dalam bentuk aset tetap. Untuk itu kami, para dosen dari Fakultas Ekonomi dan Bisnis, akan memberikan pelatihan yang rencananya akan dibagi dalam tiga tahap, yaitu: tahap perencanaan, tahap pelaksanaan, dan tahap review. Target luaran yang akan dicapai atas kegiatan pelatihan ini adalah luaran wajib berupa publikasi pada jurnal Serina dan luaran tambahan berupa HKI.